Power Efficiency of Steam Turbine Generator Switching into Thermal Circuit of Small and Medium Boiler Houses - R. I. Yesman; I. P. Yarmolchik; I. V. Rymashevski; G. V. Moroz (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper is devoted to the solution of the problem concerning power saving on the basis of small power-and-heat-supply plants.Power efficiency of power turbine generator switching into thermal circuit of small and medium boiler houses is justified in the paper.